Open-system behaviour of magmatic fluid phase and transport of copper in arc magmas at Krakatau and Batur volcanoes, Indonesia - Agangi, Andrea; Reddy, Steven (Elsevier, 2016)
The Sunda arc of Indonesia is an excellent example of how volcanic processes at convergent plate margins affect the distribution of metals and control the distribution of ore deposits. In this paper, we report microtextural observations and microanalytical data (SEM-EDS and LA-ICP-MS) of silicate and sulfide melt inclusions from fresh samples of volcanic rocks from the 2008 eruption of Mt. Krakatau and 1963 eruption of Mt. Batur, Sunda arc, Indonesia that bear implications on the concentration and transport of Cu and other chalcophile elements in mafic-intermediate magmas in arc settings. These multi-phase inclusions contain glass, amphibole and plagioclase, together with co-trapped apatite, magnetite, sulfides and lobed, drop-like Fe-oxide. We observed two stages of sulfide formation: 1) early-formed sulfide globules (pyrrhotite and intermediate solid solution), which derived from an immiscible sulfide melt and only occur as inclusions in phenocrysts; and 2) late-formed, irregular Cu-rich sulfides (intermediate solid solution to bornite), which were deposited in the presence of an aqueous fluid, and are contained as fluid phase precipitates in vapour bubbles of melt inclusions and in vesicles, as well as finely dispersed grains in the groundmass. Microtextural observations and X-ray elemental maps show that interaction between sulfide globules and aqueous fluid resulted in partial oxidation and transfer of Cu between the fluid and the sulfide phase. A compilation of whole-rock analyses from the Sunda arc indicates that Cu reaches ~ 250–300 ppm in mafic samples (SiO2 ≤ 52 wt.%), and then suddenly drops with progressive fractionation to < 50 ppm in intermediate-felsic samples.This behaviour can be explained by sulfide melt exsolution or degassing and scavenging of Cu occurring at various stages of magma fractionation (at MgO ~ 8–2.5 wt.%). These trends can be effectively modelled by sulfide saturation during fractional crystallisation at oxygen fugacities varying from fO2 = FMQ + 0.8 to FMQ + 1.4. In contrast, LA-ICP-MS analyses of whole multi-phase melt inclusions hosted in olivine, pyroxene and plagioclase indicate variable Cu and S contents (Cu up to ~ 6000 ppm), which do not correlate with fractionation indicators (e.g. SiO2, MgO, Rb), consistent with co-trapping of Cu S phases with silicate melt. The highest Cu concentrations, Cu/S and incompatible trace elements (e.g. Rb) were measured in plagioclase, which crystallised over a wider range of melt compositions in comparison with olivine and pyroxene, and preferentially contains late-formed Cu-rich sulfides. These results underline the importance of mafic-intermediate magmas as sources of Cu in magmatic-hydrothermal ore deposits, and suggest that S-rich fluid is of primary importance in the transport of Cu in arc settings.